Das Dehmelhaus in Blankenese Künstlerhaus zwischen Erinnern und Vergessen - Vogel, Carolin (Hamburg University Press, 2019)
"Dem größten deutschen Dichter wurde eine Villa geschenkt" ("The greatest German poet was given a villa") was the headline of an Italian daily newspaper in 1913. One hundred years later, Richard Dehmel's house was facing ruin. What had happened? This book reconstructs the history of an extraordinary place and its inhabitants. It commemorates two key figures of artistic modernism: the poet Richard Dehmel (1863-1920), who discovered Thomas Mann, moved Karl Schmidt-Rottluff and inspired Arnold Schönberg, and the art patron Ida Dehmel (1870-1942), who inspired writers, fought for women's rights and founded the women artists' association GEDOK. Based on letters, the book traces the transformation of the Gesamtkunstwerk Dehmelhaus from a legendary artists' meeting place to a place of remembrance. The book asks about the reasons for its disappearance and shows how the Dehmelhaus nevertheless withstood the storms of the 20th century.